Comprehensive effect of Naoxintong capsule combined with Western medicine on coronary heart disease after percutaneous coronary intervention: a meta-analysis - Yu, Liyuan; Huang, Peiying; Wang, Meida; Li, Zhishang; Cai, Hairong; Feng, Yuchao; Wu, Lulu; Peng, Weihang; Zeng, Jing; Chen, Bojun (Frontiers in Pharmacology, 2024)
Aims: To systematically evaluate the comprehensive effect of combining Naoxintong capsule (NXT) with Western medicine (WM) on coronary heart disease post-percutaneous coronary intervention (PCI). Methods: Randomized controlled trials (RCTs) of NXT for patients with CHD after PCI were systematically searched across multiple databases, including the Cochrane Library, PubMed, Embase, Chinese National Knowledge Infrastructure (CNKI), Chinese Science and Technology Journal Database (VIP), and Wan Fang, from inception until January 31, 2023. Study selection, data extraction, and quality assessment were performed by two independent reviewers. The quality of the included studies was evaluated using version 2 of the Cochrane risk-of-bias tool (RoB 2), and data analysis was performed using R4.2.2. Results: Fifteen RCTs conducted between 2011 and 2022 and involving 1,551 patients were identified, with 774 and 777 patients in the experimental and control groups respectively. It was found that the NXT and WM combination was superior to the WM therapy alone in terms of the effective clinical rate (odds ratio [OR] = 4.69, 95% confidence interval [CI] = 2.13-10.30), effective rate in electrocardiogram (OR = 6.92, 95% CI = 3.44-13.92), effective rate in angina (OR = 5.90, 95% CI = 3.04-11.46), left ventricular ejection fraction (mean difference [MD] = 4.94, 95% CI = 2.89-6.99), brain natriuretic peptide (MD = -294.00, 95% CI = -584.60 to -3.39), creatine kinase-MB (MD = -7.82, 95% CI = -13.26 to -2.37), major adverse cardiovascular events (OR = 0.24, 95% CI = 0.14-0.43), maximum platelet aggregation rate (MD = -8.33, 95% CI = -11.64 to -5.01), and Chinese medicine evidence score (OR = 9.79, 95% CI = 3.57-26.85). However, there was no significant difference in cardiac troponin I level reduction (MD = -0.13, 95% CI = 0.35-0.09) or the occurrence of adverse medicine events (OR = 0.92, 95% CI = 0.41-2.05). Meta-regression and subgroup analyses indicated that NXT capsule dosage, treatment duration, and patient baseline characteristics contributed to the heterogeneity. Conclusion: A combination of NXT and WM can improve clinical outcomes in patients undergoing PCI. However, further studies are needed to confirm the reliability and safety of this combined treatment approach.